Neurocriminology and the Next Generation of Criminological Theory: Integration, Limits, and Ethical Risks - Zul Khaidir Kadir (Punggawa Legacy Center, 2026)
Neurocriminology has increasingly been presented as a route toward “next generation” criminological theory, yet its integration has often been accompanied by conceptual overreach, weak causal inference, and ethically risky policy translation. This article examined how neuro-level evidence could be incorporated into criminological explanation without reducing crime to biology or converting correlational findings into institutional certainty. A theory-oriented qualitative synthesis was used to map integration pathways with core criminological traditions, to clarify the epistemic limits of brain–behavior inference, and to identify the principal ethical risks arising in criminal justice settings. The analysis found that neurocriminology strengthened theory when it specified mechanisms linking exposure to action, clarified heterogeneity in susceptibility and desistance, and refined broad constructs such as self-control, strain, and social learning. The analysis also found that reverse inference, ecological validity constraints, confounding, and base-rate problems sharply limited individual-level prediction and courtroom interpretation. Ethical risks were concentrated in biological branding, bias amplification, privacy erosion, and the expansion of coercive governance under the banner of scientific objectivity. A disciplined, multi-level integration was therefore identified as the most defensible pathway for theory development and policy use.